2015
DOI: 10.1002/joc.4459
|View full text |Cite
|
Sign up to set email alerts
|

Recent temperature variability and change in the Altiplano of Bolivia and Peru

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…For example, the temperature increased by 0.15 to 0.25 • C·decades −1 over the 1965 to 2012 period [1]. ETp and ETr involved the same climatological factor for their estimation.…”
Section: Etp Etr and Rainfall Analysismentioning
confidence: 99%
“…For example, the temperature increased by 0.15 to 0.25 • C·decades −1 over the 1965 to 2012 period [1]. ETp and ETr involved the same climatological factor for their estimation.…”
Section: Etp Etr and Rainfall Analysismentioning
confidence: 99%
“…This was observed in many parts of the world and for various climate variables and indices, such as minimum temperature (López-Moreno et al, 2016), precipitation (Rosas et al, 2016;Vuille et al, 2003), diurnal temperature range (Jaswal et al, 2016;New et al, 2006), and extremes indices (Skansi et al, 2013;You et al, 2013). Certain trend differences may be expected even on short spatial scales due to factors such as topography and feedback processes (You et al, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…For instance, studies have found stronger positive trends in maximum than minimum temperatures since the middle of the 20th century in the Bolivian and Peruvian Altiplano (e.g. López-Moreno et al, 2016), and Alexander et al (2006) detected a decrease in the number of warm nights in the same region. These findings are not in accordance with the globally observed and expected increase in night-time temperatures and the decrease in the diurnal temperature range (Alexander et al, 2006;Donat et al, 2013b;IPCC, 2013;Morak et al, 2011;New et al, 2006;QuintanaGomez, 1999;Vincent et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the approach is currently being implemented in several weather services [e.g. Météo‐France, the Norwegian Meteorological Institute, MeteoSwiss, the Irish Meteorological Service Met Éireann, and the Slovenian Environment Agency (Vertačnik et al ., )], and it is already applied in countries where station networks are sparse such as Bolivia (Vicente‐Serrano et al ., ; López‐Moreno et al ., ) or Tanzania (Luhunga et al ., ).…”
Section: Introductionmentioning
confidence: 99%